Factors Determine Purchase Intention of Green Product - Ihwan Susila; Setia F. Fitriani; Anton A. Setyawan; Syamsudin (International Journal of Psychosocial Rehabilitation, 2020)
This study aimed to analysis the relationships between social influence, attitude, environmental knowledge, recycling participation, eco-labelling, environmental exposure, perceived value, and purchase intention of green products. Data was collected from 151 customers of cosmetics product, fashions, foods, motor cycles, fuels, and furniture in Indonesia through structured survey questionnaire. Data was analyzed based on multiple regression analysis. The results show indication of significant relationships between social influence, recycling participation, eco-labelling, environmental exposure, perceived value, and purchase intention of green products. However, customer’s intention to purchase green products were not identified to have significant relationship with attitude and environmental knowledge. The discussion present suggestions for researches and marketers with interest in consumers’ behavior in green product.